Emotional Freedom as a Concept and Technique in Psychotherapy: Kebebasan Emosional sebagai Konsep dan Teknik dalam Psikoterapi - Al-Fhadee, Ammar Talal Hamdullah (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Emotional regulation plays a critical role in mental health, influencing psychological resilience and social well-being. Specific Background: Many individuals suppress their emotions due to social, academic, or personal pressures, resulting in long-term psychological distress, impaired relationships, and reduced self-awareness. Knowledge Gap: Despite the recognition of emotional regulation’s importance, limited attention has been given to holistic, accessible methods like Emotional Freedom Technique (EFT) in addressing emotional suppression and trauma in non-clinical populations. Aims: This study aims to explore the concept of emotional freedom and evaluate the efficacy of EFT as a complementary intervention for emotional regulation and psychological healing. Results: Findings from the literature indicate that EFT contributes to stress reduction, improved emotional expression, enhanced self-control, and alleviation of trauma-related symptoms through its integration of acupressure and cognitive focus. Novelty: This study synthesizes psychological theory with energy-based interventions, offering a novel perspective on how EFT supports emotional liberation by restoring physiological and emotional balance. Implications: The findings suggest that incorporating EFT into therapeutic and self-help contexts could provide a low-cost, non-invasive, and effective tool for enhancing emotional resilience and overall mental well-being, particularly in populations underserved by conventional psychological services. Highlights: EFT offers affordable, accessible emotional healing for non-clinical populations. Combines acupressure and cognition to regulate suppressed emotions. Fills research gap in holistic emotional regulation methods. Keywords: Emotional Regulation, Emotional Freedom Technique, Mental Health, Psychological Healing, Holistic Intervention